From 3D spheroids to tumor bearing mice: efficacy and distribution studies of trastuzumab-docetaxel immunoliposome in breast cancer - Rodallec, Anne (Int J Nanomedicine, 2018)
PURPOSE: Nanoparticles are of rising interest in cancer research, but in vitro canonical cell monolayer models are not suitable to evaluate their efficacy when prototyping candidates. Here, we developed three-dimensional (3D) spheroid models to test the efficacy of trastuzumab-docetaxel immunoliposomes in breast cancer prior to further testing them in vivo. MATERIALS AND METHODS: Immunoliposomes were synthesized using the standard thin film method and maleimide linker. Two human breast cancer cell lines varying in Her2 expression were tested: Her2+ cells derived from metastatic site: mammary breast MDA-MB-453 and triple-negative MDA-MB-231 cells. 3D spheroids were developed and tested with fluorescence detection to evaluate viability. In vivo efficacy and biodistribution studies were performed on xenograft bearing nude mice using fluorescent and bioluminescent imaging. RESULTS: In vitro, antiproliferative efficacy was dependent upon cell type, size of the spheroids, and treatment scheduling, resulting in subsequent changes between tested conditions and in vivo results. Immunoliposomes performed better than free docetaxel + free trastuzumab and ado-trastuzumab emtansine (T-DM1). On MDA-MB-453 and MDA-MB-231 cell growth was reduced by 76% and 25%, when compared to free docetaxel + free trastuzumab and by 85% and 70% when compared to T-DM1, respectively. In vivo studies showed tumor accumulation ranging from 3% up to 15% of the total administered dose in MDA-MB-453 and MDA-MB-231 bearing mice. When compared to free docetaxel + free trastuzumab, tumor growth was reduced by 89% (MDA-MB-453) and 25% (MDA-MB-231) and reduced by 66% (MDA-MB-453) and 29% (MDA-MB-231) when compared to T-DM1, an observation in line with data collected from 3D spheroids experiments. CONCLUSION: We demonstrated the predictivity of 3D in vitro models when developing and testing nanoparticles in experimental oncology. In vitro and in vivo data showed efficient drug delivery with higher efficacy and prolonged survival with immunoliposomes when compared to current anti-Her2 breast cancer strategies.